Malformations of the midline commissures: MRI findings in different forms of callosal dysgenesis. - Küker, W; Mayrhofer, H; Mader, I; Nägele, T; Krägeloh-Mann, I (2003)
Malformations of the corpus callosum (CC) may occur in many different syndromes. Various forms have been observed. We report seven cases of malformation of the CC. Special attention is directed towards the development of the fornix and hippocampus as a hippocampal commissure is a prerequisite of normal hippocampal development. The clinical disability of the patients presented here differed significantly, which may in part be due to the different extent of this cerebral malformation. The relevance of the concomitant aplasia of the limbic system has not been addressed in detail previously in the literature.